2020
DOI: 10.3389/fsurg.2020.507954
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Unilateral Approach for Bilateral Decompressive Endoscopic Spinal Surgery for Lumbar Stenosis to Improve Back and Leg Pain: A Consecutive Single-Center Series of 60 Patients

Abstract: Introduction: Endoscopic surgery is one of the methods that achieve the goal of decompression while minimizing collateral tissue damage. Its efficacy and safety have been supported by numerous studies. There is a plethora of studies on lumbar stenosis regarding the outcomes and related issues in endoscopic spine surgery. However, few studies evaluated the outcome of the decompressive lumbar spine surgery. The present study aims to analyze the outcome of a unilateral approach to endoscopic surgery for lumbar st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Previous studies have reported that clinical outcomes of interlaminar full-endoscopic laminectomy are not different from those of conventional laminectomy [ 13 15 , 19 22 ]. However, the previous studies are limited by their retrospective or single-center designs [ 4 , 13 15 , 20 , 21 , 23 25 ]. In this trial, the quality of the evidence will be improved as adequate sample sizes, blinded assessments, and prospective registration from multiple centers will be used to reduce bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that clinical outcomes of interlaminar full-endoscopic laminectomy are not different from those of conventional laminectomy [ 13 15 , 19 22 ]. However, the previous studies are limited by their retrospective or single-center designs [ 4 , 13 15 , 20 , 21 , 23 25 ]. In this trial, the quality of the evidence will be improved as adequate sample sizes, blinded assessments, and prospective registration from multiple centers will be used to reduce bias.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the clinical outcomes of interlaminar full-endoscopic laminectomy are not different from those of conventional laminectomy [ 13 15 , 19 22 ]. However, all previous studies comparing interlaminar full-endoscopic laminectomy and conventional open laminectomy are retrospective or single-center prospective studies [ 4 , 13 15 , 20 , 21 , 23 25 ]; therefore, a multicenter, randomized controlled trial (RCT) is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic spine surgery has been evolving rapidly in the past decades, starting from contraindications and eventually becomes feasible for lumbar stenosis. Due to the wide range of treatable lumbar stenosis and the reported favorable clinical outcomes, the endoscopic posterior approach has attracted more and more attention [ 17 - 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the wide range of treatable lumbar stenosis and the reported favorable clinical outcomes, the endoscopic posterior approach has attracted more and more attention. [17][18][19][20][21][22] As we all know, the outside-in technique was most accepted in the LE-ULBD surgery, 23 whose procedure involves removal of bony structure including the lamina, articular facet joint first, then the entire LF en bloc or piecemeal to expose the dura and nerve root. However, the outside-in technique has disadvantages including uncertain removal border, dura tear and nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…Using the MacNab criteria, 88.4% showed excellent to good outcomes. A unilateral percutaneous endoscopic approach to perform bilateral decompression for patients with lumbar stenosis is both safe and effective 8 .…”
Section: Lumbar Stenosis Spondylolisthesis and Clinical Outcomesmentioning
confidence: 99%